Sociocultural Influences on the Transmission of HIV From Husbands to Wives in Cambodia: The Male Point of View. (July 2017) - Yang, Youngran; Thai, Sopheak
The purpose of the study was to explore, within cultural and societal contexts, the factors of spousal HIV transmission as described by the experiences of HIV-positive Cambodian men. Using qualitative research methods, the researchers collected data from in-depth interviews with 15 HIV-positive Cambodian men of seroconcordant couples recruited from an HIV/AIDS clinic in Phnom Penh. Using a model of HIV transmission from husbands to wives, the questions were designed to elicit the men's perspectives on the topics of promiscuity, masculinity, condom use in marriage, the image of the ideal Cambodian woman, and attitudes toward sex and marriage. Directed content analysis was used to analyze the interview data. The main results were as follows: (a) men involved with sex workers perceived this as a natural behavior and a necessary part of being an approved member in a male peer group, (b) married men never used condoms during sex with their wives prior to their HIV diagnosis, (c) men perceived a good wife as one who is diligent and loyal to her husband, and (4) men's attitudes toward sex and marriage (e.g., sex perceived as a part of life pleasure) differed from those of their wives. Promoting honest spousal communication about sexuality, maintaining men's marital fidelity, and increasing women's comfort in the use of sexual techniques are suggested as strategies for reducing HIV transmission within marriage in Cambodia. Future interventions should focus on reshaping men's behaviors and changing cultural norms to protect them and their spouses from HIV infection.